Menyulut Aksara Gunungpati : Memadukan Literasi dan Inklusi Sosial - Heru Eko Prasetyo; Wawan Wibisono; Puji Setya Sunarka (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2025)
Low interest in reading and limited access to digital literacy in Gunungpati Village, Semarang, are the main challenges in developing community literacy, especially among children and teenagers. The community service program